Scouting Program as a Strategy to Cultivate Early Discipline Habits in Elementary School Students - Nurhaifa; Ikhsanul Hakim; Nabila Safitri (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
Student discipline encompasses not only compliance with school rules and punctuality but also the development of positive habits that can be cultivated through scouting activities. This study aims to explore the role of scout leaders in shaping students’ disciplined practice habits through scouting programs. The research employs a qualitative approach with a case study design to investigate the coaching practices at the SD Negeri Pulias Abaling scout post in depth. Seven respondents were purposively selected as the primary subjects, representing diverse perspectives on participation and involvement in scouting activities. The results indicate that most indicators of discipline reached high levels, including adherence to training schedules (80%), compliance with leaders’ instructions (87%), consistency in active participation (92%), responsibility for equipment and training tasks (87%), and respectful and orderly behavior during activities (93%). The aspect of independence in completing training tasks showed the lowest achievement (77%), indicating the need to strengthen self-reliant habits. These findings reinforce the understanding that scouting guidance is effective in developing student discipline and have implications for designing more systematic and sustainable training programs in schools.